Curriculum development in Ethiopia vis-à-vis Patrick Slattery’s postmodern curriculum principles: A reflection - Tadesse Melesse Meraw; Esuyawkal Tessema Ageze (Bahir Dar Journal of Education, 2023)
This article revisits curriculum development in the Ethiopian context vis-à-vis Patrick Slattery’s postmodern views of curriculum development principles (rejection of metanarratives, the artificial bifurcations, the interconnectedness of individual experiences in a global context, the assertion and validation of everyone’s voice in the school community and understanding of the complexity of metaphysics) using critical review and discursive analysis. For this purpose, the different time education initiatives, education policies, education sector development programs, and general education curriculum development frameworks were reviewed. The findings unveil that behavioristic, linear and objective-oriented, ideological or hegemonic, competitive, and patriarchal features shadowed curriculum development in Ethiopia. The Cartesian dualism of Western and Tylerian rationale metanarrative; bifurcation of students in ability groups and learning outcomes; the abandonment of different voices (mainly educated professionals) in curriculum development; the rejection of important values, religious and cultural thoughts in the pretext of secular education; and the detachment of indigenous and value education from Ethiopian schooling stipulate postmodern perspective in developing curriculum. Despite the rhetorical representation of postmodern viewpoints in educational policy, the current practical operation is also scant. Hence, the article implies some useful lessons to deconstruct and construct critical issues while developing curricula in the Ethiopian education system.